Asphalt modiification with red grape pomace as an antioxidant material - Rojas Rojas, Gabriel (2025)
This study evaluated the antioxidant properties of red grape pomace and its benefits as an additive for asphalt binder. The samples were modified using red grape pomace as an antioxidant agent in concentrations of 1%, 2% and 3%. These samples were left outdoors to undergo natural oxidation for 12 weeks. Another set of samples were aged in an ultraviolet radiation (UV) chamber to compare the results between both oxidation methods. Three functional groups were taken in consideration to measure the degree of oxidation: the carbonyl, the carbon-carbon double bond and the sulfoxide indexes. The asphalt modified with 3% red grape pomace had the lowest increase in carbonyl index, showing that the additive works as an agent to delay the oxidation process in asphalt. The indexes obtained for the field aged samples were significantly larger than the ones associated to the UV chamber, consequently aging in a UV chamber did not properly emulate environmental conditions. Further research analyzing higher percentages of red grape pomace (greater than 3%) to understand the effect of larger contents of additive is recommended.